TORAKOCHIRURGIAResults of pneumonectomy in non-small cell lung cancer patients - Gibas, Artur; Chwirot, Piotr; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Pneumonectomy in non-small cell lung cancer (NSCLC) patients results in high morbidity and mortality and thus indications for this procedure should be limited. Unfortunately, because of late diagnosis, pneumonectomy is performed in 10-30% of all lung resections in NSCLC. Material and Methods: Four hundred and forty-six (31%) pneumonectomies were performed in 1439 NSCLC patients operated on between 1993 and 2000 in the Department of Thoracic Surgery of the Medical University of Gdansk. Median age was 64 years (36-78). Thirty patients (6.7%) received perioperative oncological treatment. Results: Median survival was 16 months while 5-year survival was recorded in 116/446 (26%) patients. In 36/446 patients (8.1%) thirty-day or in-hospital death was recorded. Complications occurred in 177 (39.7%) patients. Pathological stage was the strongest negative predictor of survival (p < 0.0001). Median survival in months according to pathological stage was as follows: Ib – 41, IIb – 22, IIIa – 14, IIIb – 11. Median survival in patients with large cell carcinoma, adenocarcinoma and squamous cell carcinoma was 6, 12 and 21 months respectively (p = 0.03). Patients lived longer after left pneumonectomy (21 versus 12 months, p = 0.002). Neither age (p = 0.45), comorbid diseases (p = 0.33) nor other risk factors (p = 0.34) had a negative impact on survival. These factors were associated with higher rate of postoperative complications (p < 0.0001). Conclusions: A man older than 67, with right sided large cell carcinoma that has stage higher than IIa, is the worst candidate for pneumonectomy concerning complications and long-term survival. Thus, pneumonectomy is a procedure of high risk of death and complications with a poor long-term survival and should be limited only to selected patients.